Answers

2014-01-28T19:20:53+05:30
3x+2y=41.................(1)
2x+3y=14...................(2)
now (1)*2-(2)*3  we get
 6x+4y=82
-6x-9y=-42
     -5y=40
       y=-8
putting y=-8 in(1) we get
3x+2*(-8)=41
x=19

0
2014-01-28T19:21:54+05:30
Multiply eq.1 by 2,
2(3x+2y)=(41)2
multiply eq.2 by 3,
3(2x+3y)=(14)3
eq.1   6x+4y=82
eq.2(-)6x+9y=42
_______________
              -5y=40
                y=-8
and x=19.
0
The main motto of using elimination method is to make the coefficient of x or y same in both the equation so the we can eliminate them and then find out the value of remaining variable.
Sorry wasn't meant for u Strovey just a help for the questionar by mistake wrote it here.